Haedyozhnost sorevnovatelnoj deyatelnosti v nastolnom tennise - Matytsin, O. V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of the study was the scientific and technologic substantiation of the control and correction of the competition activities in table tennis. The elite table tennis players of the world (n=15) and Russia (n=23) acted as the subjects of our research. The next modeling characteristics where offered and investigated: the activity, the result-producting activity, the general effectiveness, the efficiency of a pitch and of their receiving, the result producting-activity in extreme situation, the tendency of the repeated result, the variability of a result producting-activity.